2021
DOI: 10.30630/ijasce.3.2.53
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Internet of Things (IoT) in Construction Industry: Building a Better Future

Abstract: Construction companies today are aiming for the finest technologies to achieve their targets in minimum cost possible along with a high level of security and safety. Construction companies are focusing more on the benefits of internet in their projects in order to improve processes, reduce waste and optimally utilize their resources and Internet of Things (IoT) is making it possible in a much more efficient way than thought of. IoT has now become the newest of the technology that is being used in the construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…According to Tables 5 and it can be observed that the initial six components account for 65.8 % of the overall variance present in the data. The residual constituents exhibit significantly reduced eigenvalues and contribute a lesser proportion of the variability [ 1 , 40 , 52 ]. This analysis facilitates determining the optimal number of components retained in the final exploratory factor analysis model.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tables 5 and it can be observed that the initial six components account for 65.8 % of the overall variance present in the data. The residual constituents exhibit significantly reduced eigenvalues and contribute a lesser proportion of the variability [ 1 , 40 , 52 ]. This analysis facilitates determining the optimal number of components retained in the final exploratory factor analysis model.…”
Section: Results and Analysismentioning
confidence: 99%
“… Cost-benefit analysis and surveys Limited focus on knowledge-related barriers. [ [52] , [53] , [54] ] 7 Examines IoT integration in building maintenance, emphasizing its benefits. Literature review and field surveys Minimal exploration of creativity-related hurdles.…”
Section: Related Workmentioning
confidence: 99%